Penerapan Model Contextual Teaching and Learning Dalam Meningkatkan Kemampuan Menulis Eksposisi - Elis Hasanah; Iis Ristiani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The aim of this research is to explore the impact of using the Contextual Teaching and Learning (CTL) model on the expository writing skills of class VI students at SDN Bangbayang 2 Elementary School. This research is based on the low level of expository text writing skills of elementary school students, students tend to be less interested in practicing writing. Students consider writing activities to be a difficult task. Problems that often occur in writing activities are the inability to use punctuation, spelling, diction, sentence structure and written content, so it is certain that the results will not be in accordance with the expected competence. The research used an experimental design with a control and experimental group, the experimental group consisted of 30 students at SDN Bangbayang 2 and the control group consisted of 35 students at SDN Bangbayang 1. Data was collected through written tests before and after the intervention. The results showed that the experimental group experienced a significant increase in the average posttest score compared to the pretest, while the control group only showed a slight increase in the posttest and pretest. The conclusion of this research is that the integration of the Contextual Teaching and Learning (CTL)model is effective in improving students' expository writing skills.